Adolescents' Understanding of What Causes Emotional Distress: A Qualitative Exploration in a Non-clinical Sample Using Ideal-Type Analysis - O'Neill, Alisha; Stapley, Emily; Stock, Sarah; Merrick, Hannah; Humphrey, Neil (Frontiers in Public Health, 2021)
Abstract Background There is increased interest in early intervention and prevention of mental health difficulties during adolescence; thus, we are seeing increased efforts to optimise wellbeing during this epoch. Positive emotional experiences are a central component of overall wellbeing. However, research exploring what adolescents perceive to be the cause(s) of their emotional difficulties is lacking. Improving understanding of this issue within non-clinical adolescent groups may provide useful insight into how to develop strategies to support young people as they navigate emotional difficulties Objectives The aim of this research was to explore if meaningful categories of perceived cause(s) for emotional distress exist for non-clinical adolescent groups. Methods The data for this study were drawn from interviews across 6 sites in England conducted as part of the 5-year national evaluation of (blinded for review). The sample comprised of 32 young people aged 11-12 years from the first annual wave of qualitative data collection in 2017. Ideal type analysis – a qualitative form of person-centred analysis – was used to construct a typology of adolescents perceived cause(s) for emotional distress. Findings We identified five distinct categories of perceived cause: 1) perceived lack of control; 2) unfair treatment; 3) others, their actions and judgements as the catalyst; 4) concerns for self and others; and, 5) self as cause. Conclusions Our findings illustrate that distinct categorises for perceived cause of emotional distress exist among adolescents considered to be ‘at risk’ of developing mental health difficulties, which provides a foundation for future necessary work seeking to investigate the possible link between perceived cause for emotional distress and help-seeking behaviour among sub-clinical groups.